Interaction effect of co-digestion sewage sludge and food waste for production of biogas - Hosen, Md Sabuj; Mansor, Mariatul Fadzillah; Mohd Ali, Ainoor Mariana; Alam, Md Zahangir (IIUM Press, 2020)
Increasing population, urbanization and industrial activities have increased the amount of solid waste worldwide. Food waste (FW) and sewage sludge (SS) are some of the solid wastes. Co-digesting of both substrates may improve process stabilization to increase biogas production and overcome the nutrients imbalance. Thus, anaerobic co-digestion has been recognized as a technology that could provide a clean renewable energy source and help reducing the landfill problem. In this study, the interaction between FW and SS as co-substrates in anaerobic digestion was studied under mesophilic temperature 36C (± 0.5). The experiments were conducted using five batch reactors with different ratios of substrates. There are four different analyses used to identify the characteristics of FW and SS, which are pH, reducing sugar (RS), total solid (TS), and total carbohydrate (TC). Water displacement method was used to record biogas yield. The experimental results showed that the highest biogas yield was from the composition of 50:50 (FW: SS) with a biogas volume of 1150.14 mL, while the least was the composition of 0:100 (FW: SS) with 170.47 mL biogas produced. The results for substrate degradation showed that the composition of 100:0 (FW: SS) has the highest percentage degradation for reducing sugar with the percentage of 56%, while the minimum was 0:100 (FW: SS) with a percentage of 35%. Besides, for TC, the highest percentage of degradation was the composition 50:50 (FW: SS) with 84%, and the least was 0:100 (FW: SS) with 44%. This study proves that using FW and SS enhanced biogas production as well as reducing the current issues of waste disposal.